Exploring agronomic diversity and disease tolerance in soybeans to combat Cowpea mild mottle virus - H. Kuswantoro; S. Zubaidah; E. Uge; K. Rozana; P. Purwantoro; J. Purnomo (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The yield of soybeans is affected by the performance of agronomic traits and the presence of abiotic and biotic environmental stresses. The utilization of pesticides to alleviate biotic environmental stressors results in environmental deterioration. One of the biotic environmental stresses is virus disease caused by Cowpea mild mottle virus. Identifying the main factors influencing yield and selecting traits resistant to virus infection can assist development programs in creating soybean varieties with enhanced Cowpea mild mottle virus tolerance. The soybean lines can face one of the biotic environmental stresses. Soybean varieties are susceptible to a range of biotic environmental challenges. This investigation sought to examine the diversity in agronomic traits and disease resistance, with the goal of identifying the top-performing soybean varieties for controlling Cowpea mild mottle virus disease.METHODS: The plant materials were 1000 soybean lines originating from 26 crosses. Each line was planted in rows and inoculated with Cowpea mild mottle virus naturally using the Bemisia tabaci vector. To set up the experiment, a population of Bemisia tabaci carrying the Cowpea mild mottle virus was established in the field, enabling natural biotic environmental stress of the plants by the virus infection. The identification of the lines was conducted through an assessment of agronomic characteristics and an analysis of the relationship between these characteristics and their susceptibility to Cowpea mild mottle virus. The attributes that had a substantial impact on the principal component analysis biplot and their correlation with seed yield per plot were initially identified  as selection criteria.FINDINGS: Soybean plants displayed diverse agronomic characteristics and disease ratings. Rather than relying on resistance, their defense mechanism against diseases involved tolerance. The variation in soybean characteristics can be attributed mainly to factors such as seed yield, the quantity of filled pods, and the number of productive pods per plant. Additionally, plant height showed the strongest correlation among these traits. The selected 100 soybean varieties displayed outstanding agronomic characteristics and resistance to diseases, leading to a decrease in the need for pesticides and contributing to environmental conservation.CONCLUSION: Soybean seed yield is influenced by agronomic traits and biotic environmental stress such as virus disease, with significant diversity observed among the tested lines. The attributes that had the most significant impact were the amount of productive nodes, quantity of filled pods, and seed yield per plant. Plant height consistently showed a strong correlation with seed yield. Seed yield per plant had a positive correlation with the disease score, making it unsuitable as a selection criterion. This positive correlation has been observed, indicating that soybeans possess a mechanism of tolerance that enables them to sustain optimal seed yields even when infected by a virus. The criteria for selecting 100 superior soybean lines included the number of filled pods, number of nodes, and plant height, which were deemed suitable for the evaluation process. The use of 100 selected soybean lines can reduce pesticide usage while maintaining environmental quality and supporting sustainable agriculture.